Tourism social media transformations in identity, community and culture - Munar, Ana María; Gyimóthy, Szilvia; Cai, Liping A. (Emerald, 2013)
This volume addresses the transformative power of tourism social media and offers novel theoretical and methodological approaches to its academic investigation. Acknowledging the collective value creation mechanisms of new media, the authors explore how technology nurtures, augments and modifies social or commercial interactions in tourism. The book emphasizes the role of fantasy and imagination in fluid tourism experiences and critically scrutinizes contested concepts pertaining to human interaction in cyberspace, such as equality, anonymity, transparency, democratization, and publicity culture. The chapters summon insights from media studies, actor-network theory, communicative action and symbolic convergence among others, and offer a palette of emerging methods suitable for academic enquiries of virtual worlds. The theoretical grounding, empirical evidences, and interdisciplinary analysis of the anthology expand the actual research agenda and shed light on conceptual tensions and ambiguities in the present literature. As such, Tourism social media : transformations in identity, community and culture contributes to increasing research reflexivity in tourism studies at large.
Keywords: Tourism -- Social aspects.; Hospitality industry -- Social aspects.; Social media.; elektronické knihy; electronic books